Islamic Banking Acceleration in Malaysia and Indonesia: Panel VAR Approach - Arif Widodo; Mohammad Adam Haekal (Li Falah: Jurnal Studi Ekonomi dan Bisnis Islam, 2019)
Islamic banking acceleration has been the major theme discussed for years, indicating the importance of such topic to be reexamined comprehensively. This study is aimed to empirically examine several aspects and condition which may play a leading role in accelerating (preventing) the growth of Islamic bank in two countries, namely Malaysia and Indonesia. To that end, this study attempts to incorporate selected internal bank condition and macroeconomic situation in a single model to exhibit the dynamics relationship between both and the total asset of Islamic banking. In terms of methodology, this study employs the dynamic panel model that is expected to be able to address the research questions. The result of this study demonstrates that both third party fund and financing-to-deposit ratio are proven to be effective in accelerating the Islamic banking asset, as opposed by the non-performing financing ratio that has a negative impact on it. Moreover, it becomes apparent the acceleration of Islamic bank share is heavily dependent upon the real sector growth represented by GDP yet the monetary variables (interest rate and exchange rate) remains the serious problem for Islamic bank to foster the growth. This implies that the real sector is valuable contributor to the share of Islamic bank compare to monetary condition.